Fatayat NU Sebagai Sumber Kemajuan Perempuan di Tengah Persaingan Dunia : (Pimpinan Cabang Fatayat NU Kota Bogor) - Kholifatul Husna Asri; Suimah Herniawati (Neolectura, 2023)
The opening of opportunities and opportunities for women in various fields and aspects makes it easier for women to increase competitiveness. PC Fatayat NU Bogor City has a big role in the effort to create strong generations of Indonesian women. Women are the hope of the nation as a superior and competitive generation. This research focuses on how to empower women through Fatayat NU which is needed to support professionalism and competitiveness in facing world competition. The design in this study uses a qualitative research type, with data taken through interviews by researchers to key informants regarding related problems and becoming the focus of systematic and in-depth discussion. The results of the study indicate that Fatayat NU has a major and important role in cultural change with the capabilities possessed by the chairman as its leader. The empowerment of women or PC Fatayat NU members in Bogor City is carried out through various activities carried out. Through the role of PC Fatayat NU, Bogor City is expected to produce strong and superior women to answer and face world competition as a form of women's progress